Assessment of Weekday and Weekend Variations on Ground Level Ozone and Nitrogen Dioxide Concentration in Jeli, Kelantan - Nurul Azman, Nur Alya Arisha; Norrimi Rosaida Awang; Hanafia, Zakiah Hanim (Journal of Sustainable Natural Resources, 2025)
This study examines the variations in ground-level ozone (O?) and nitrogen dioxide (NO?) concentrations between weekdays and weekends in Jeli and their relationship with traffic volume. Data were collected over two weeks in August 2024 using the Aeroqual S500 device and manual traffic counting. The results showed that NO? concentrations were lower on weekends, with median values ranging from 20 to 40 parts per billion (ppb), while O? concentrations were higher (15–30 ppb) compared to weekdays (10–20 ppb). This trend was attributed to reduced nitrogen monoxide emissions and enhanced photochemical reactions under lower NO? conditions. Traffic volume was significantly higher on weekdays, peaking during morning (7–9 a.m.) and evening (4–6 p.m.) rush hours, with Class 1 vehicles averaging 400 vehicles/hour on weekdays and 300 vehicles/hour on weekends. Consequently, NO? concentrations were higher on weekdays (60–80 ppb median values, peaking at 140 ppb). Statistical analyses, including T-tests, indicated no significant differences in mean concentrations between weekdays and weekends. Pearson correlation analysis confirmed a moderate positive relationship between traffic volume and NO? (0.410), while O? levels were influenced by sunlight intensity and atmospheric chemistry. These findings highlight the impact of traffic emissions on NO? and the importance of photochemical processes in O? variations, emphasising the need for effective air quality management strategies.